(untitled) (International Journal of Engineering and Computer Science, 2015)
This paper proposes a TDMA-based multichannel medium access control (MAC) protocol for QoS provisioning in mobile ad hoc networks (MANETs) that enables nodes to transmit their packets in distributed channels. The IEEE 802.11 standard supports multichannel operation at the physical (PHY) layer but its MAC protocol is designed only for a single channel. The single channel MAC protocol does not work well in multichannel environment because of the multichannel hidden terminal problem. Our proposed protocol enables nodes to utilize multiple channels by switching channels dynamically, thus increasing network throughput. Although each node of this protocol is equipped with only a single transceiver but it solves the multichannel hidden terminal problem using temporal synchronization. The proposed energy efficient multichannel MAC (EM-MAC) protocol takes the advantage of both multiple channels and TDMA, and achieves aggressive power savings by allowing nodes that are not involved in communications to go into power saving “sleep mode”. We consider the problem of providing QoS guarantee to nodes as well as to maintain the most efficient use of scarce bandwidth resources. Our scheme improves network throughput and lifetime significantly, especially when the network is highly congested. The simulation results show that our proposed scheme successfully exploits multiple channels and significantly improves network performance by providing QoS guarantee in MANETs.